2013
DOI: 10.3802/jgo.2013.24.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors associated with local recurrence in squamous cell carcinoma of the vulva

Abstract: ObjectiveTo analyze the prognostic factors related to the recurrence rate of vulvar cancer.MethodsRetrospective study of 87 patients diagnosed of vulvar squamous cell carcinoma diagnosed at a tertiary hospital in Madrid between January 2000 and December 2010.ResultsThe pathological mean tumor size was 35.1±22.8 mm, with stromal invasion of 7.7±6.6 mm. The mean free margin after surgery was 16.8±10.5 mm. Among all patients, 31 (35.6%) presented local recurrence (mean time 10 months; range, 1 to 114 months) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15] The results of this study also verified that LN involvement was clearly confirmed as being the most important prognostic factor for both DFS. In the multivariate analysis, LN involvement was the independent prognostic factor regarding DFS in the current study.…”
supporting
confidence: 73%
See 3 more Smart Citations
“…[7][8][9][10][11][12][13][14][15] The results of this study also verified that LN involvement was clearly confirmed as being the most important prognostic factor for both DFS. In the multivariate analysis, LN involvement was the independent prognostic factor regarding DFS in the current study.…”
supporting
confidence: 73%
“…10 Iacoponi et al reported higher recurrence rate (43.6%) in a study of 87 patients with a median age of 73 years and median tumor size of 35.4 mm. 7 Higher incidence of recurrence might be attributed to the presence of older patients and bigger tumors in that study. On the other hand, Woelber et al reported the recurrence rate as only 13.6% in a study of 109 patients 56% of whom had tumor less ≤ 2 cm in greatest diameter.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…[3][4][5] Although several studies aimed to report the safety and long-term oncologic effectiveness or even less demolitive procedures existed, [3][4][5][6] only few investigations investigated possible risk factors for developing failure and often did not subdivide for the occurrence of different patterns of failure (ie, local, regional, and distant). [6][7][8] Hence, in the present study we aimed to report predictors of failure in squamous cell VC. In addition, we sought to describe outcomes of a consecutive series of squamous cell VC, and how the introduction of sentinel node biopsy and less radical vulvar surgery influenced long-term survival outcomes.…”
mentioning
confidence: 99%